Could the two-minute step test be an alternative to the six-minute walk test for patients with systolic heart failure?. (29th August 2020) - Węgrzynowska-Teodorczyk, Kinga; Mozdzanowska, Dagmara; Josiak, Krystian; Siennicka, Agnieszka; Nowakowska, Katarzyna; Banasiak, Waldemar; Jankowska, Ewa A; Ponikowski, Piotr; Woźniewski, Marek
Abstract: Background: The consequence of exercise intolerance for patients with heart failure is the difficulty climbing stairs. The two-minute step test is a test that reflects the activity of climbing stairs. Design: The aim of the study design is to evaluate the applicability of the two-minute step test in an assessment of exercise tolerance in patients with heart failure and the association between the six-minute walk test and the two-minute step test. Methods: Participants in this study were 168 men with systolic heart failure (New York Heart Association (NYHA) class I–IV). In the study we used the two-minute step test, the six-minute walk test, the cardiopulmonary exercise test and isometric dynamometer armchair. Results: Patients who performed more steps during the two-minute step test covered a longer distance during the six-minute walk test ( r  = 0.45). The quadriceps strength was correlated with the two-minute step test and the six-minute walk test ( r  = 0.61 and r  = 0.48). The greater number of steps performed during the two-minute step test was associated with higher values of peak oxygen consumption ( r  = 0.33), ventilatory response to exercise slope ( r  = −0.17) and longer time of exercise during the cardiopulmonary exercise test ( r  = 0.34). Fatigue and leg fatigue were greater after the two-minute step test than the six-minute walk test whereas dyspnoea and blood pressure responses were similar. Conclusion: The two-minute step test is well tolerated by patients with heart failure and may thus be considered as an alternative for the six-minute walk test.